Late Pennsylvanian vegetation changes in the Donets Basin: syndynamic aspect - Boyarina, Nataliia (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2022)
The purpose of the article. The article is devoted to the study of one from forms of syndynamics in Late Pennsylvanian time, namely phytocoenogenesis. The study of the phytocoenogenesis of ancient plant communities, i.e., the formation of new types of palaeophytocoenoses, is based on the research of vegetation diversity that is reflected in the ecological-floristic classification of the Late Pennsylvanian phytocoenoses of the Donets Basin by the Brown-Blanquet method.Material and research methods. The phytocoenogenetic researches consisted of the analysis of the changes of the species and syntaxonomic composition of vegetation cover throughout the Late Pennsylvanian. The peculiarities and main factors of phytocoenogenesis have been identified on the palaeosyntaxa in rank of the orders of the following vegetation types: wetland forests and woodlands of coastal lowlands, wetland forests and woodlands of deltaic plains, seasonally dry woodlands of river valleys and lagoon coasts. The palaeophytocoenotic data are based on the plant fossil assemblages from lacustrine, lacustrine-swamp, lacustrine-deltaic, floodplain-lacustrine, floodplain and lacustrine-lagoon deposits in more than 17 localities and 11 boreholes located within the Bakhmutska and Kalmius-Toretska troughs.Research results. Based on the analysis of the phytocoenogenetic processes (progressive and regressive development of plant communities) and the manifestations of phytocoenogenesis (formation of new communities and loss of old communities) in the development of the Late Pennsylvanian vegetation, three models of the formation of new communities and one model of the loss of communities from vegetation cover have been proposed. Each of the models reveals the relationship between the phytocoenogenetic processes and environmental changes. The evolution-progression model reflects the progressive development of palaeophytocoenoses that is expressed by the appearance of evolutionary new coenopopulations in the conditions of the expansion of landscape types (expanding biotopes). The migration-progression model conforms to the progressive development of palaeophytocoenoses as a result of the migration of plants from decreasing landscape types to expanding ones (expanding biotopes). The substitution-regression model is consistent with the regressive development of palaeophytocoenoses along with structure simplification and dominant substitution of plant communities due to the contraction of certain landscape types (decreasing biotopes). The elision-regression model of the loss of communities reflects the regressive development of palaeophytocoenoses that is expressed by the decrease in the number of coenopopulations and the number of individuals in remaining coenopopulations in the conditions of the contraction of some landscape types (decreasing biotopes).The scientific novelty. For the first time, the Late Pennsylvanian vegetation dynamics (syndynamic) have been studied. The proposed three models of the formation of new communities and one model of the loss of communities reveal the main directions in evolution of palaeophytocoenoses and give the first ideas about phytocoenogenesis in late Palaeozoic times.